1989
DOI: 10.1038/bjc.1989.351
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastrointestinal non-Hodgkin's lymphoma in a population-based registry

Abstract: Summary In a population-based registry of 580 patients with non-Hodgkin's lymphoma (NHL) 54 patients had a primary gastric lymphoma, 42 an intestinal, 113 a primary extranodal lymphoma localised elsewhere than in the gastrointestinal tract and 371 a primary nodal NHL. Histological specimens were reviewed by a panel of pathologists and classified according to the Kiel classification and the International Working Formulation. The 4-year survival rates for primary gastric, intestinal, other extranodal and nodal N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
2
5

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 20 publications
(26 reference statements)
5
38
2
5
Order By: Relevance
“…These differences may have been associated with the difference in response to treatment and patient survival. A better prognosis for gastric lymphoma compared with other localizations has been described previously, 1,4,8,11,17,18,21,24,25 although several authors showed no difference in the prognosis between gastric lymphoma and intestinal lymphoma. 5,9,[13][14][15]19,20,22,23 Few publications have shown prognostic data on patients with both gastric and intestinal involvement.…”
Section: Discussionmentioning
confidence: 50%
“…These differences may have been associated with the difference in response to treatment and patient survival. A better prognosis for gastric lymphoma compared with other localizations has been described previously, 1,4,8,11,17,18,21,24,25 although several authors showed no difference in the prognosis between gastric lymphoma and intestinal lymphoma. 5,9,[13][14][15]19,20,22,23 Few publications have shown prognostic data on patients with both gastric and intestinal involvement.…”
Section: Discussionmentioning
confidence: 50%
“…Patients with a digestive site discovered during staging investigations of a NHL were excluded from the study. The mesenteric localizations were considered to be primary intestinal NHL in accordance with the literature (Otter et al, 1989aWeingrad et al, 1982Dragosics et al, 1985).…”
Section: Materials and Methods Patientsmentioning
confidence: 83%
“…Only two population-based series of gastrointestinal nonHodgkin's lymphomas (NHL) have been described (Otter et al, 1989a;D'Amore et al, 1994). The …”
mentioning
confidence: 99%
“…In our study the malignant lymphomas were not especially prone to disagreements with respect to histologic type. We ascribe this to the fact that the Netherlands Cancer Registry uses the ICD-0 and has developed special codes for the histology of malignant lymphomas (Otter, 1989).…”
Section: Discussionmentioning
confidence: 99%